2021
DOI: 10.1001/jamanetworkopen.2021.11613
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Delayed Surgical Treatment and Oncologic Outcomes in Clinical Stage I Non–Small Cell Lung Cancer

Abstract: IMPORTANCEThe association between delayed surgical treatment and oncologic outcomes in patients with non-small cell lung cancer (NSCLC) is poorly understood given that prior studies have used imprecise definitions for the date of cancer diagnosis. OBJECTIVE To use a uniform method to quantify surgical treatment delay and to examine its association with several oncologic outcomes. DESIGN, SETTING, AND PARTICIPANTSThis retrospective cohort study was conducted using a novel data set from the Veterans Health Admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 34 publications
2
74
0
2
Order By: Relevance
“…Conversely, the time between preoperative diagnostic CT imaging and surgical treatment was reported to be associated with an increased risk of recurrence. 14 Patients who underwent surgical treatment within 12 weeks of diagnosis had better overall survival than those who underwent procedures that were delayed for more than 12 weeks. 14 The total of 123 days for pre-visit, pre-diagnosis, and pre-treatment times encountered by patients in our study undergoing surgery could increase the risk of recurrence or poor prognosis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the time between preoperative diagnostic CT imaging and surgical treatment was reported to be associated with an increased risk of recurrence. 14 Patients who underwent surgical treatment within 12 weeks of diagnosis had better overall survival than those who underwent procedures that were delayed for more than 12 weeks. 14 The total of 123 days for pre-visit, pre-diagnosis, and pre-treatment times encountered by patients in our study undergoing surgery could increase the risk of recurrence or poor prognosis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]7,12,13 Black patients with early-stage lung cancer are more likely to experience treatment delays 4,14,15 and have higher mortality rates than White patients. 4,6,7,14,[16][17][18][19][20][21] Black race is associated with lung cancer treatment delays averaging 6.7 days. 13 Factors contributing to delays in timely care include inadequate access to specialty care, poor care coordination, and poor patient-provider communication.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Similar to this study, some studies have investigated the consequences of the delayed start of the treatment in the OS. Heiden et al 16 have found that for each week of surgical delay beyond 12 weeks, the risk for recurrence increased by 0.4% (HR = 1.004; 95% CI: 1.001-1.006; p = 0.002), and those with surgical treatment within 12 weeks of diagnosis had significantly better OS than the patients with procedures delayed more than 12 weeks (HR = 1.132; 95% CI: 1.064-1.204; p < 0.001). Samsom et al 17 have found that delayed surgery was associated with increased 30-day mortality (2.9% vs. 2.4%; p = 0.01) and decreased median survival (57.7 ± 1.0 vs. 69.2 ± 1.3 months; p < 0.001), related to nondelayed Stage-I NSCLA patients, respectively.…”
Section: Discussionmentioning
confidence: 99%